Synthesis of Aryl Nitriles via Aerobic Oxidative Cleavage of Aryl C=C Bonds with (NH4)2CO3 as the Nitrogen Source - Zheng, Yi; Liu, Wenbo; Tian, Xinzhe; Ren, Yun-Lai (Synlett, 2022)
An aerobic oxidative method was developed for conversion of arylethenes to aromatic nitriles using (NH4)2CO3 as the nitrogen source and Cu(NO3)2 as the catalyst. The present method allowed a series of arylethenes to underwent oxidative cleavage of C=C bonds to give the targeted products in low to high yields. In addition, the present conditions are compatible with many groups such as alkyl, alkoxy, N,N-dimethylamino, chloro, bromo, iodo, ester, cyano group, and so on.
Keywords: aromatic nitriles; arylethenes; carbon–carbon double bonds; oxidative cleavage; oxygen